Analisis tindak tutur lokusi, ilokusi dan perlokusi dalam film kartun kisah Imam Syafi’i berdasarkan perspektif John L. Austin - Ni'mah, Maftuhah Salamatun (Maliki Interdisciplinary Journal, 2024)
This research is entitled analysis of locutionary, illocutionary and perlocutionary speech acts in Imam Syafi'i's cartoon based on the perspective of John L. Austin. Speech act is a language phenomenon that involves speakers and speech partners. Each speech will be different depending on the situation, place, time, speaker, speech partner, speech context and when the utterance occurs. The aim of this research is to analyze locutionary, illocutionary and perlocutionary acts in the cartoon imam Syafi'i and to explain the functions of the three types of speech acts. The research method used is qualitative research, while the data analysis uses the Miles and Huberman models, which consist of three stages, namely data reduction, data presentation and drawing conclusions. The theoretical foundation in this study is the perspective of John L. Austin, namely the classification of speech acts into three types, locutionary, illocutionary and perlocutionary. The results of the study found five locutions in the form of giving information, outpouring, advising, praying, and clarifying. The four illocutions are apologizing, asking, hoping, and calling. The five Perlocutions are thanking, opposing, insulting, convincing, and upsetting.